HbA(1c) Standardisation: History, Science and Politics - John, W Garry (The Australian Association of Clinical Biochemists, 2007)
Significant analytical improvements have occurred since glycated haemoglobin (GHb), measured as total HbA(1), was first used in routine clinical laboratories around 1977. Following the publication of the Diabetes Control and Complications Trial (DCCT) study in 1993 the issue of international standardisation became an important objective for scientists and clinicians. The lack of international standardisation led several countries to develop national standardisation programs. The International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) Working Group on Standardisation of HbA(1c) established a true international reference measurement system for HbA(1c) and the successful preparation of pure HbA(1c) calibration material that should lead to further improvements in inter-method and inter-laboratory variability. Reporting of HbA(1c) has been agreed using the units of mmol/mol (IFCC) and percent (National Glycohemoglobin Standardization Program, NGSP).